Degradation and physical properties of sugar palm starch/sugar palm nanofibrillated cellulose bionanocomposite - Atikah M.S.N.; Ilyas R.A.; Sapuan S.M.; Ishak M.R.; Zainudin E.S.; Ibrahim R.; Atiqah A.; Ansari M.N.M.; Jumaidin R. (Industrial Chemistry Research Institute, 2023)
Biomolecules; Biopolymers; Degradation; Enamels; Field emission microscopes; Homogenization method; Nanocomposites; Reinforcement; Scanning electron microscopy; Starch; Bio-nanocomposite; Field emission scanning electron microscopy; Homogenization process; Homogenizers; Nanofibrillated cellulose; Reinforcement materials; Soil burial degradation; Solution-casting method; Cellulose; Cellulose; Degradation; Homogenizers; Reinforcement; Scanning Electron Microscopy; Starch